Fibrinolysis during liver transplantation: analysis by the Thrombodynamics method. Issue 9 (11th April 2019) - Roullet, Stéphanie; Labrouche, Sylvie; Freyburger, Geneviève
Abstract : An issue in orthotopic liver transplantation (OLT) is the diagnosis of hyperfibrinolysis. The Thrombodynamics-4D assay (TD4D) is a videomicroscopy system allowing the dynamic analysis of fibrin clot. Fibrinolysis is highlighted by a change in clot intensity. The aim of this observational study was to evaluate the TD4D as a tool to diagnose fibrinolysis during OLT. Thirty consecutive patients were included. We studied a subset of 41 samples from 13 patients who demonstrated hyperfibrinolysis during OLT by global fibrinolytic capacity studied by the Lysis Timer (GFC/LT) and/or euglobulin clot lysis time (ECLT) and/or EXTEM maximum lysis (EXTEM ML) on ROTEM. Three samples exhibited fibrinolysis. They exhibited significantly shorter ECLT, higher lysis on EXTEM graphs, shorter GFC/LT clot lysis time and higher t-PA activity values. After adding urokinase, 13 samples exhibited fibrinolysis. In conclusion, TD4D allows the dynamic analysis of fibrin clot formation and lysis. It only recognises the most severe forms of hyperfibrinolysis during OLT.